“Hi This Is NESTORE, Your Personal Assistant”: Design of an Integrated IoT System for a Personalized Coach for Healthy Aging - Palumbo, Filippo; Crivello, Antonino; Furfari, Francesco; Girolami, Michele; Mastropietro, Alfonso; Manferdelli, Giorgio; Röcke, Christina; Guye, Sabrina; Salvá Casanovas, Antoni; Caon, Maurizio; Carrino, Francesco; Abou Khaled, Omar; et al. (Frontiers in Digital Health, 2020)
In the context of the fourth revolution in healthcare technologies, leveraging monitoring and personalization across different domains becomes a key factor for providing useful services to maintain and promote wellbeing. This is even more crucial for older people, with ageing being a complex multi-dimensional and multi-factorial process which can lead to frailty. The NESTORE project was recently funded by the EU Commission with the aim of supporting healthy older people to sustain their well-being and capacity to live independently. It is based on a multi-dimensional model of the healthy ageing process that covers physical activity, nutrition, cognition, and social activity. NESTORE is based on the paradigm of the human-in-the-loop cyber-physical system that, exploiting the availability of Internet of Things technologies combined with analytics in the cloud, provides a virtual coaching system to support healthy ageing. This work describes the design of the NESTORE methodology and its IoT architecture. We first model the end-user under several domains, then we present the NESTORE system that, analyzing relevant key-markers, provides coaching activities and personalized feedback to the user. Finally, we describe the validation strategy to assess the effectiveness of NESTORE as a coaching platform for healthy ageing.